1983
DOI: 10.1007/bf01641080
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the mannose-resistant and mannose-sensitive haemagglutinins of Escherichia coli isolated from urinary tract infections

Abstract: The distribution of mannose-resistant (MRHA) and mannose-sensitive (MSHA) fimbrial haemagglutinins was examined in 482 strains of Escherichia coli isolated from 390 adult women and 45 pregnant mothers with a variety of urinary tract infections (UTI), and from 47 healthy controls. The proportion of MRHA strains was significantly higher in patients with symptomatic UTI (75%) than in women with non-significant bacteriuria (30%, p less than 0.001), pregnant women with asymptomatic UTI (34%, p less than 0.0001) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1985
1985
1994
1994

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…However, using more-sensitive methods and morecareful patient selection, others have found evidence of fimbriation and adherence in bacteria in a substantial proportion of urine specimens from infected patients (313,390,427) (181,198,338,469,470,472,509,512,518,527). Hemagglutination testing yields similar results, with the highest proportion of MRHA strains among pyelonephritis patient isolates (50 to 81%) and progressively lower proportions among cystitis patient isolates (17 to 52%), ABU patient isolates (11 to 19%), and fecal isolates (2 to 29%) (48, 49,102,139,162,181,315,316,354,399,423,509,566). This evidence indicates that mannose-resistant uroepithelial-cell adherence and MRHA are characteristic of strains with an increased ability to cause UTI (especially the more clinically severe forms) and suggests that these properties may contribute directly to urovirulence.…”
Section: Epidemiology and Animal Studiesmentioning
confidence: 71%
“…However, using more-sensitive methods and morecareful patient selection, others have found evidence of fimbriation and adherence in bacteria in a substantial proportion of urine specimens from infected patients (313,390,427) (181,198,338,469,470,472,509,512,518,527). Hemagglutination testing yields similar results, with the highest proportion of MRHA strains among pyelonephritis patient isolates (50 to 81%) and progressively lower proportions among cystitis patient isolates (17 to 52%), ABU patient isolates (11 to 19%), and fecal isolates (2 to 29%) (48, 49,102,139,162,181,315,316,354,399,423,509,566). This evidence indicates that mannose-resistant uroepithelial-cell adherence and MRHA are characteristic of strains with an increased ability to cause UTI (especially the more clinically severe forms) and suggests that these properties may contribute directly to urovirulence.…”
Section: Epidemiology and Animal Studiesmentioning
confidence: 71%
“…Both kinds of pili have been demonstrated on UTI-causing E. coli strains [34,52,54]. Pili I-expressing bacteria attach to mannose-containing uromucoid, mainly Tamm-Horsefall protein [33].…”
Section: C) Bacterial Fimbriaementioning
confidence: 99%
“…Furthermore, MS pill cause agglutination of guinea-pig erythrocytes whereas MR pili agglutinate human red blood cells [34]. It has been shown that MR pili recognize P blood group antigens within the human erythrocyte membrane [52].…”
Section: C) Bacterial Fimbriaementioning
confidence: 99%
See 2 more Smart Citations